Estimation of protein contamination in latex - Aftab Alam (Rubber World, 1996)
Latex contains a significant amount of water soluble proteins. Latex products such as gloves, condoms and surgical blooms come into contact with humans and contaminating proteins pose health risks. Latex protein is easily absorbed through the skin and can trigger allergic responses. Because of this health risk associated with latex protein, latex-based products likely to come into contact with humans require removal of the protein and careful monitoring of the protein content of the finished product. This study has shown that the dotMetric protein assay is highly reproducible and simple to perform. It has been compared to the standard Lowry method generally used for estimation of protein in latex products and found to be more sensitive in that it detected as little as 5mg/ml of protein.
Keywords: Latex; Protein contamination